Sport Motivation, Physical Activity, and Sustainable Lifestyle Behavior among Community Runners: Evidence from Tasikmalaya, Indonesia - Aang Rohyana; Cucu Hidayat; Agus Arief Rahmat; Endah listyasari; Ida Wahidah (Gladi : Jurnal Ilmu Keolahragaan, 2026)
This study examined the relationships among sport motivation, exercise self-efficacy, running attitude, community support, physical activity, and sustainable lifestyle behavior among members of a running community in Tasikmalaya City. Growing participation in running communities offers opportunities to promote active and sustainable lifestyles, yet the psychological and social mechanisms underlying these behaviors remain insufficiently explored. A quantitative approach with an explanatory correlational survey design was employed. The sample consisted of 120 running community members selected through purposive sampling. Data were collected using questionnaires and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4. The findings revealed that sport motivation significantly influenced exercise self-efficacy, running attitude, and community support. In turn, exercise self-efficacy, running attitude, and community support significantly predicted physical activity. Physical activity also showed a significant positive effect on sustainable lifestyle behavior. The model demonstrated satisfactory predictive power, explaining 57.4% of the variance in physical activity and 46.5% of the variance in sustainable lifestyle behavior. These findings indicate that sport motivation serves as a key driver of physical activity through psychological and social pathways, ultimately fostering sustainable lifestyle behavior. The study contributes to sport psychology literature and provides practical evidence for developing community-based physical activity promotion programs.